Rapid T2-weighted turbo spin echo MultiVane brain MRI using compressed SENSE: a qualitative analysis. Issue 10 (October 2021) - Sartoretti, E.; Wyss, M.; Eichenberger, B.; van Smoorenburg, L.; Binkert, C.A.; Sartoretti-Schefer, S.; Sartoretti, T.
Highlights: Non-cartesian MRI sequences can be combined with Compressed Sensing technology. A novel Compressed Sensing PROPELLER MRI sequence implementation is feasible. A Compressed Sensing PROPELLER MRI sequence implementation shortens scan times.